OPTION VALUATION WITH MATHEMATICA - Ong Yih Ying; Anton Abdulbasah Kamil; Mohamad Faisal Abdul Karim (Program Studi Statistika Unisba, 2009)
Studies in option pricing have became more important and challenging in financial area becauseoption valuation can add significant information to the decision making process. In this study weattempt to establish the American and European call option. Call option gives the buyer the right, butnot the obligation to buy a specified stock at a predetermined price on or before a predetermined date.An American option may be exercised earlier before the expiration date. For European options, earlyexercise is not possible. It can only be exercised only at maturity. In this paper, we do mathematicalexperiments to solve the problem of financial valuation using Mathematica.